EXPERIENCE PREFERENCES IN RECREATIONAL AND COMPETITIVE ACTIVITIES REGARDING MOTIVATIONAL ORIENTATIONS - Ivana Duvnjak, (Sport Scientific And Practical Aspects, 2026)
Hedonic and eudaimonic pursuits are two main approaches to a full life. Hedonic activities are pursued for pleasure and comfort, while eudaimonic activities are pursued to use or develop one’s strengths. These two perspectives can be studied as orientations, which refer to motives, values, and goals. Leisure activities are important for quality of life because they allow people to meet their needs and values. This research aimed to contribute to a comprehensive understanding of how experience preferences fit into the framework of motivational orientation. In this study, we examined how these orientations might apply within recreational and competitive activities in leisure time. A total of 241 adult anglers between 18 and 70 years participated in the research. Respondents gave their estimates about experience preferences, motivational orientations, and life satisfaction. A theoretical model was established on the relationship between hedonic and eudaimonic motivational orientation, experience preferences, and life satisfaction. Then, the adequacy of the model fit was examined. Results show a strong effect of motive for achievement on eudaimonic orientation. Significant effect was found for environment and escaping stressors motive on both hedonic and eudaimonic orientation. Also, the type of activity has a moderate effect on the motive for achievement. Only eudaimonic orientation has an effect on life satisfaction.